HERODOTUS SCYTHIANS HISTORY: DETAILS OF NEW READING - Sergey L. Dudarev (Вестник Северо-Кавказского федерального университета, 2022)
The article analyzes the study of Ukrainian scientists V.Y. Murzin and S.V. Petkov, considering the events of Scythian history as presented by the « father of history» Herodotus. Appreciating the work of these experts , the author draws attention to other possible interpretations of the text of Herodotus, especially in terms of certain Scythian rituals associated with the mentality of the peoples of the pre-industrial era.